Seasonal Variation of Food Web Structure and Stability of a Typical Artificial Reef Ecosystem in Bohai Sea, China - Li, Shengpeng; Wang, Ruyue; Jiang, Yueming; Li, Yanyu; Zhu, Lin; Feng, Jianfeng (Frontiers in Marine Science, 2022)
The last 30 years have witnessed the degradation and loss of function in the ecosystem of the Bohai Sea, China. Great efforts, such as artificial reefs, have been used to restore the ecosystem of the Bohai Sea in recent years. In this study, we examined the seasonal variation of food webs in artificial reefs of Juehua Island by the Ecopath model. Results showed that the number of species, range of trophic level, energy cycle proportion, energy complexity, nutrition transfer efficiency, and ecosystem maturity have increased from summer to autumn. However, the food web stability of artificial reefs has no obvious change from summer to autumn. Loop analysis revealed that the heaviest feedback loops are the interactions among benthos, zooplankton, and phytoplankton, and the predator-prey negative interaction strength between zooplankton and phytoplankton dominated the stability of the artificial reef, whether in summer or autumn. This study suggests that stability is a more robust indicator for ecosystem assessment and could provide useful information in future restoration plans of the marine ecosystem.